PERSEPSI DAN MOTIVASI MAHASISWA PGSD FKIP UNPAS TENTANG PROFESI GURU - Murfiah, Uum (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2018)
Abstract:. Teaching profession is a noble and professional job. Becoming a noble and professional teacher requires a graduate level of education. Entering this profession begun with the perception. and the true motivation of the teaching profession. Therefore, the purpose of this study was to describe the perception and motivation of PGSD FKIP Unpas students in semester VII about the primary-school teacher profession. The method applied a qualitative approach since the researcher attempted to reveal the natural situation and social phenomenon of the case of study. Data collection techniques used the observation and interviews. The data checking was done with credibility, dependebality, and confirmability. The data analysis was done through individual case analysis. The findings of the study that the teaching profession was a job which requires competence and expertise, which should be systematically prepared since they were enrolled as students of PGSD study program until they were graduated from the program. The perception and motivation of PGSD students towards the teaching profession was increasing along with their knowledge and experience in college. The implications of this research provide a spectrum in the future for PGSD program managers to design a continuous program of teacher professional development to strengthen the identity of prospective teachers.Keyword: Perception, student motivations, teacher profession. Abstrak: Profesi guru merupakan pekerjaan yang mulia dan profesional. Menjadi guru yang mulia dan profesional membutuhkan pendidikan setingkat sarjana keguruan. Sejatinya memasuki profesi guru, diawali oleh persepsi dan motivasi yang benar terhadap profesi guru. Untuk itu, tujuan penelitian ini adalah mendeskripsikan perpsepsi dan motivasi mahasiswa PGSD FKIP Unpas semester VII tentang profesi guru sekolah dasar. Metode penelitian menerapkan pendekatan kualitatif karena peneliti berupaya mengungkap situasi alamiah dan fenomena sosial dari kasus yang diteliti. Tehnik pengumpulan data dengan observasi dan wawancara. Pengecekan data dilakukan dengan kredibilitas, dependabilitas dan konfirmabilitas. Analisis data dilakukan melalui analisis kasus individu. Temuan penelitian bahwa profesi guru merupakan pekerjaan yang membutuhkan kompetensi dan keahlian yang secara sistematis perlu disiapkan sejak menjadi mahasiswa keguruan sampai lulus dari program studi PGSD. Persepsi dan motivasi mahasiswa PGSD terhadap profesi guru meningkat sejalan dengan pengetahuan dan pengalaman yang mereka peroleh di bangku kuliah. Implikasi penelitian ini memberikan spektrum ke depan agar pengelola program studi PGSD mendesain program pengembangan profesi guru secara berkelanjutan untuk memperkokoh jati diri mahasiswa calon guru.Kata Kunci: Persepsi, motivasi mahasiswa, profesi guru.